USE OF THE EVALOBS® ADHERENCE SCALE IN AN UNSELECTED FRENCH POPULATION OF TREATED SUBJECTS WITH ANTIHYPERTENSIVE, STATINS OR ORAL ANTIDIABETICS MEDICATIONS: THE FLAHS 2017 STUDY. (June 2018) - Girerd, X.; Hanon, O.; Pannier, B.; Vaisse, B.
Abstract : Objective: A Visual Analog Scale (VAS) is useful for diagnosing medication nonadherence and its validity has been evaluated using electronic pillbox as the gold standard. We have developed the EVALOBS® scale for use on paper or on smartphone, and the aim of the study was to administrate the scale among FLAHS 2017 participants treated for an hypertension, a dyslipidemia or diabetes. In subjects treated with antihypertensive medications, participants completed the 6-item Girerd Scale and EVALOBS®. Design and method: The French League Against Hypertension Survey (FLAHS) are carried out by self-questionnaire sent by mail to individuals from the French Kantar Health sampling frame (representative panel of the population living in metropolitan France). In 2017, FLAHS was conducted in 4783 subjects aged 35 and over. The EVALOBS® has a scale from 0 to 15 and the use instruction is how many days have you taken the drug in the past 15 days. A score > 12 indicates a good compliance. The 6-item Girerd scale was also completed. Good adherence was determined for a score of 0 to 2 and nonadherence for a score of 3 or more. The agreement between EVALOBS® and the 6-item Girerd scale was evaluated in treated hypertensives. Results: The survey included 4783 subjects with 1308 treated hypertensives, 942 subjects treated with lipid-lowering drugs and 405 subjects treated with anti-diabetics. EVALOB® indicates Good adherence in 96% of subjects and the 6 questions questionnaire indicates good adherence in 95% of subjects. An excellent agreement is noted in 93.8%. An EVALOBS® score indicating nonadherence or an absence of response to EVALOBS® is observed in 3.6% [CI 95, 2.5–4.7] of hypertensives, in 6.0% [CI 95, 3.9–8.1] of diabetics and in 8.2% [CI 95, 6.5–9.9] of dyslipidemic patients. Conclusions: In the population living in France and in unselected patients treated for metabolic disease or hypertension, non-adherence is lowest for antihypertensive medications and highest for statins. EVALOBS®, which shows good agreement with an adherence questionnaire, is a quick and simple tool for assessing adherence. The smartphone app EVALOBS is available for free on Google play and the Apple store.